A Short Review Of Neural Network Techniques In Visual Servoing Of Robotic Manipulators. - Ramachandram, Dhanesh; Rajeswari, Mandava (2003)

(untitled)
Robotics is one of the most challenging applications of soft computing techniques. It is characterized by direct interaction with a real world, sensory feedback and a complex control system.